Facile synthesis of CNT cotton/ZnO nanocomposite using waste cooking oil as the biotemplate via hydrothermal/calcination process - Mohd Zobir, Syazwan Afif; Ahmad, Khairulmazmi; Ismail, Ismayadi; Md. Yusof, Juraina; Abdullah, Abdul Halim (Institut Biosains, Universiti Putra Malaysia, 2023)
One of the common domestic wastes that are abundantly available is waste cooking oil (WCO) where improper disposal will create problems such as clogging the drain and/or related sewage system. Whether this carbon-rich waste can be up-converted for the formation of CNT and/or as a biotemplating agent for the formation of ZnO-CNT nanocomposite is the subject of interest of this research work. Therefore, the focal point of this work is to use this carbon-rich waste material, WCO as a biotemplate of ZnO growth onto the surface of carbon nanotube cotton (CNTC) for the formation of CNTC/ZnO nanocomposite. The results from the physicochemical analyses showed that WCO plays a dual role; as a carbon precursor for the formation of CNTC and as a templating agent to grow ZnO in the preparation of CNTC/ZnO nanocomposite. In the latter, the WCO was attached to the surface of CNTC and acted as the nucleation site for the ZnO growth which then formed the CNTC/ZnO nanocomposite, as indicated by the presence of the COO-Zn bond in their FTIR spectra. XRD studies showed the presence of the carbon, ZnO and iron oxide phases, confirming that the resulting nanocomposite is composed of CNTC and ZnO as the main components, while the presence of iron oxide is due to the catalysts that were used for the synthesis of the CNTC. The degradation of the sp2 graphitic phase was observed in the Raman spectra, indicating the defects of sp3 became prominent, due to the formation of the COO-Zn bond.